Wildlife, National Parks and People - Pandey, Deep Narain (Indian Forester, 1993)
Habitat destruction and over exploitation are the biggest threats to the survival of plants and animals in India. Establishment of wildlife reserves has augmented the wildlife population but increasing pressure of people continue to encroach upon the natural ecosystems. The result is crop-raiding. human and livestock killing; and property destruction. The conservation efforts, thus, are at cross roads, on the one hand threatened are the ecological processes and life support systems, on the other, at stake is the security of livelihoods of the people living in and around the protected areas.The collaborative eco-development of local communities is the only answer that can help the parks and poor. The effective people’s participation is the key to the survival of wildlife.